School principal’s strategy in managing a child-friendly school: Bullying cases - Irpani, Ayit; Amrullah, Silmi; Astuti, Yani; Tirtana, Arief; Budiman, Ali Mumin; Nurrohmah, Sari (Universitas Jambi, Indonesia, 2025)
This research aimed to analyze the effect of the principal's strategy in the Child-Friendly School Program (SRA) on bullying cases. This research used a quantitative approach with a population of 411 students and a sample of 80 students. Data were collected through questionnaires and analyzed using instrument tests, partial tests, normality tests, and hypothesis tests. The research framework was based on George Edward III's theory for variable X (principal's strategy in SRA) and Migliaccio and Raskauskas' theory for variable Y (bullying cases). The results showed that the school principal's strategy in the SRA Program had an influence of 20.2% on bullying cases, while other factors outside this research influenced the remaining 78.9%. In conclusion, although the principal's strategy in the SRA program contributes to reducing bullying cases, other factors also influence it. This research underlines the importance of the school principal's role in creating a safe and supportive school environment for students' development.